Gen Z Talent Mangement; Expectations, Motivation and Challenges in Human Resource Management - Rina Masruroh; Deri Prayudi; Nico Irawan; Oding Syafrudin (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2026)
This study aims to identify work expectations, analyze motivation factors, and reveal organizational challenges in managing gen z talent in Kuningan Regency. The research methode use a mixed methode approach through a survey of 147 Gen z respondents and in-depth interviews with 8 HR managers. The results show that Genn Z’s work expectation include work flexibility (87,8%), a collaborative environment (82,3%), career development (79,6%), and competitive compensation (76,2%). The dominant motivational factors are recognition of achievement (mean 4,21), work life balance (mean 4,18), and learning opportunities (mean 4,12). The main challenges include the technology gap, resistance to traditional work culture, and limited development programs. This study produced an adaptive Gen Z Talent Management Model with four strategic pillars that can be applied in the context of local organization.